2019
DOI: 10.1371/journal.pone.0217393
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of CD99 and its ligand upregulates IL-6 and TNF-α upon T cell activation

Abstract: CD99 has been reported to be involved in T cell regulation. CD99 ligand involvement in the regulation of T cell activation has been postulated. In this study, recombinant CD99 proteins were produced and used as a tool for determining the role of CD99 and its ligand interaction. Recombinant CD99 proteins induced the upregulation of IL-6 and TNF-α expression, but not IFN-γ, in anti-CD3 monoclonal antibody activated T cells. The cytokine alteration was not observed in unstimulated T cells indicating the cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
(41 reference statements)
1
22
0
Order By: Relevance
“…Ligation of CD99 on the activated T cells by a CD99 recombinant protein, increased production of proinflammatory cytokines, including interleukin-6 (IL-6) and TNF-α. Engagement of CD99 on monocytes and natural killer cells also resulted in the increased production of IL-6 and TNF-α (Takheaw et al 2019). Waclavicek et al demonstrated resting T cells in response to CD99 stimulation and T cell receptor (TCR) activation, proliferate and produce IFN-γ and TNF-α, (Waclavicek 1998).…”
Section: Cluster Of Differentiation 99 (Cd99)mentioning
confidence: 99%
“…Ligation of CD99 on the activated T cells by a CD99 recombinant protein, increased production of proinflammatory cytokines, including interleukin-6 (IL-6) and TNF-α. Engagement of CD99 on monocytes and natural killer cells also resulted in the increased production of IL-6 and TNF-α (Takheaw et al 2019). Waclavicek et al demonstrated resting T cells in response to CD99 stimulation and T cell receptor (TCR) activation, proliferate and produce IFN-γ and TNF-α, (Waclavicek 1998).…”
Section: Cluster Of Differentiation 99 (Cd99)mentioning
confidence: 99%
“…The β isoform is expressed at higher levels on Natural Killer (NK) cells, B cells, T cells, dendritic cells, granulocytes and macrophages, while the α-isoform is expressed at very low levels on NK cells [27]. Takheaw et al showed that the interaction of a recombinant CD99 with its ligand on immune cells upregulated the production of pro-inflammatory cytokines [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that putative CD99 ligands were expressed on the surfaces of monocytes, NK cells and dendritic cells, but not on those of B and T cells [ 14 ]. Recombinant CD99 protein enhanced the upregulation of IL-6 and TNF-α expression by T cells, monocytes and NK cells [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated that putative CD99 ligands were expressed on the surfaces of monocytes, NK cells and dendritic cells, but not on those of B and T cells [ 14 ]. Recombinant CD99 protein enhanced the upregulation of IL-6 and TNF-α expression by T cells, monocytes and NK cells [ 14 ]. The presence of undefined CD99 ligands on leukocyte surfaces as well as regulation of the immune response via interaction between CD99 and its ligands has been suggested [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation